Implementation of Ethics of Using Artificial Intelligence in the Education System in Indonesia - Musidiansyah Otto Syaidina; Rifqi Fahrudin; Indah Ainun Mutiara (Blockchain Frontier Technology, 2024)
The use of Artificial Intelligence (AI) in education is a rapidly evolving field with the potential to transform teaching and learning. However, its implementation brings various ethical and practical challenges that must be carefully considered. Key aspects include ensuring student data privacy, promoting fairness and inclusivity in access to technology, maintaining transparency in AI algorithms and decision-making processes, and determining the appropriate levels of human control. Furthermore, accessibility for all students, including those with special needs, must be prioritized, alongside evaluating the potential long-term effects on cognitive, social, and emotional development. Given the complexity of these issues, a thoughtful and ethical approach to integrating AI into education requires ongoing collaboration among various stakeholders, including educators, AI developers, policymakers, students, and the broader community. The goal of this collaboration is to ensure that AI is used in ways that not only improve educational outcomes but also uphold fairness, equity, and transparency. It is crucial to address concerns such as data privacy, algorithmic bias, and the potential negative effects of AI on vulnerable groups to ensure the technology serves as an inclusive tool for education. This research adopts a qualitative approach to explore the different aspects of AI in education, aiming to identify and analyze its potential benefits. By examining the implications of AI integration, the study seeks to provide valuable insights into how AI can be effectively and ethically applied in education, ensuring it enhances learning while respecting core educational values and human dignity.